Bringing Disability Into the Discussion: Examining Technology Accessibility as An Equity Concern in the Field of Instructional Technology. Issue 2 (3rd April 2019) - Shaheen, Natalie L.; Lohnes Watulak, Sarah
Abstract: This article presents a review of the literature, pertaining to technology accessibility in K–12 schools in the United States, in order to bring technology accessibility into conversations about equity in instructional technology with the goal of ensuring that disabled learners have equal access to the technology-enhanced learning opportunities that are an increasingly integral part of K–12 education. The findings of the review indicate that despite long-standing federal and state accessibility mandates, inaccessible technologies abound in K–12, denying disabled learners equal access to education. We conclude that technology accessibility is an equity concern that must be prioritized in instructional technology discourse, research, and practice to begin addressing the inequality that disabled learners face in technology-enhanced K–12 learning environments. (Keywords: instructional technology, equity, disability, accessibility, K–12, education)